Türk sendika tarihinden bir örnek: devrimci işçi sendikaları konfederasyonu - Ulukan, Umut (My University, 2003)
When we look at the Turkish Trade union movement, trough the process begun at the end of 1940's, it is seen that, with the effect of trade union law acceptance, many trade unions and federations were founded . In accordence with these developments , efforts have started in order to found a central labour organization -a confederation-. In 1952, this aim was fulfilled with the foundation of Confederation of Trade Unions of Turkey (Turk-Is). In 1960's and mid 60's there were disagreements with understading of unionism in Turk-Is and this conflicts made Turkish labour movement divided. After that some of trade unionists left Turk-Is and founded DISK in 1967. The aim of this study to analyze the foundation process of DISK and its impact of the Turkish union movement in the development of 35 years. Analyzing this process, also gives us expand perspective of Turkish labour economics and industrial relations. The study consisted of three chapters and the research scheme constructed with a historical perspective. According to this the first chapter focuses on the period from early 1900's to 1960. The period of 1960-1980 is examined in second chapter. In this chapter main subjects are: foundation process of DISK, growth process of DISK and confined of DISK by military Junta. The last chapter is focuses on 1980-2002 and presents the differences of DISK in two period (1960- 1980 ; 1980 to date).
Keywords: Sendikalar